Experiments on burst pressure and fragment dispersion effects of small-sized pressure vessel BLEVE. (1st October 2020) - Li, Xuan; Liu, Zhenyi; Li, Mingzhi; Li, Pengliang; Zhao, Yao; Wan, Song
Highlights: Prefabricated fragments were added to the small-sized pressure vessel BLEVE experiments. Influence of the groove shape on the burst pressure. The relationship between the fragment distribution range and the fragment radial and axial dispersion azimuth angles. The velocity and hazards of the prefabricated fragments. Abstract: With the purpose of researching the bursting of a small-sized pressure vessel containing high pressure carbon dioxide (CO2 ) and the dispersion and distribution of the prefabricated fragments, experimental tests were conducted for pressure vessels with V-shaped grooves and X-shaped grooves. Depending on the experimental results, the rupture positions of the two types grooved pressure vessels were different, and the resistance to the pressure of the V-shaped grooved pressure vessels was higher than the resistance to the pressure of the X-shaped grooved pressure vessels. The maximum burst pressure and the average burst pressure of the V-shaped grooved pressure vessels were both higher than those of X-shaped grooved pressure vessels. For the distribution range of the prefabricated fragments, the fragments were concentrated in the range of the fragment radial scattering azimuth angles from −15° to 15° and the axial scattering azimuth angles was from 65.77° to 113.02°. The initial velocity of a fragment was 272.79 m/s, and the prefabricated fragment with that initial velocity had a residual specific kinetic energy of 101.97 J/cm 2 when it dispersed beyond 7 m, which could cause damage to organisms.